The Effect of Knowledge Sharing, Work Motivation, Work Environment, and Job Satisfaction on Em-ployee Performance - Rahmawati, Umi Deviyana; Violinda, Qristin; Sumastuti, Efriyani (ARRUS Journal of Social Sciences and Humanities, 2025)
This study was conducted with the aim of analyzing the influence of Knowledge Sharing, Work Motivation, Work Environment, and Job Satisfaction upon Employee Performance at the Public Works, Water Resources, and Spatial Planning Agency of Central Java Province. The research sample consisted of 108 staff members, who were chosen utilizing a purposive sampling technique. Information collected via questionnaires underwent analysis through the application of a multiple linear regression model. Results from the analysis reveal that, individually, Knowledge Sharing, Work Environment, and Job Satisfaction have a positive and significant influence on Employee Performance, whereas Work Motivation did not demonstrate a significant impact. When assessed together, the four variables show a significant effect on Employee Performance, yielding a coefficient of determination valued at 48.8%, which illustrates the extent to which these independent variables can account for variations in performance. This study recommends that the Agency maintain a conducive work environment and foster a culture of knowledge sharing and job satisfaction to elevate employee performance. Although not statistically significant, sustaining work motivation is still deemed crucial for preserving morale in routine task execution.